PRACTICAL ASPECTS OF ADMINISTRATIVE PLANNING AND CONTROL IN PROJECT MANAGEMENT - ATAMANIUK, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article conducts a comprehensive scientific inquiry into administrative planning and control practices within project management, conceptualizing them as an integrated system of organizational procedures, standardized documentation protocols, and strategic managerial interventions. Unlike traditional functional approaches, this study offers an original interpretation of administrative activities as the "structural backbone" of project resilience. The author posits that effective administration is not merely a supportive function but a proactive regulatory mechanism designed to synchronize project objectives with strict temporal, qualitative, and financial constraints. The research introduces a proprietary conceptual model of the «Administrative Planning-Control Cycle». This model transcends the linear progression of tasks by integrating a continuous feedback loop that links documentation flow with real-time decision-making. By categorizing key practices, specialized tools, and organizational measures, the study identifies specific administrative levers that significantly enhance project performance. The scientific novelty lies in the synthesis of rigid bureaucratic accountability with agile management principles, creating a hybrid framework capable of mitigating systemic risks. Furthermore, the article provides evidence-based recommendations for implementing this administrative framework across both public and private sectors. Special emphasis is placed on the Ukrainian context, where the administrative environment is characterized by a transition from traditional hierarchical structures to flexible governance. The findings are uniquely adapted to the specificities of public administration and the operational realities of small and medium-sized enterprises in Ukraine. The study concludes that the institutionalization of standardized administrative procedures is a prerequisite for project success in volatile socio-economic environments, providing a scalable roadmap for practitioners and policy-makers alike.
Keywords: project management; planning administrative practices; control; ISO 21500; public administration